ЩОДЕННЕ ЖИТТЯ ТА РЕЛІГІЙНІ СВЯТА В РУМУНІЇ У КОМУНІСТИЧНИЙ ПЕРІОД| DAILY LIFE AND RELIGIOUS HOLIDAYS IN ROMANIA DURING THE COMMUNIST PERIOD - Daniela IANCU (Актуальні питання суспільних наук та історії медицини, 2017)
Даніела Янку. Щоденне життя та релігійні свята в Румунії у період комунізму. У дослідженні зроблено спробу проаналізувати особливості святкування основних релігійних свят у комуністичний період у Румунії, що постає метою пропонованої студії. Методологія обіймає історично-ретроспективний аналіз, метод прямого опису польових матеріалів. Новизна дослідження полягає у доведенні ідеї, що мінімізація святкування традиційних свят у Румунії була однією з цілей Комуністичної партії, оскільки обрядодії та народні свята, окрім своїх першочергових функцій, релігійних, культурних, естетичних, комічних, мають також важливі етнічні, громадські функції. Висновки. Комуністичні лідери прагнули, щоб християнські звичаї та ритуали зникли з побуту населення, але вони були законсервовані суспільством у своїх щоденних святкуваннях, фестивальних діях, обрядодійствах календарного циклу, у весільних та поховальних обрядах тощо.Daniela Iancu. Daily life and religious holidays in Romania during the communist period. This study tries to expose the situation of the main religious holidays during the communist period in Romania. In Roumania, we know that the religious holydays were one of the targets targeted by the Communist Party, because they hold, besides their well-known functions – religious, cultural, playful, aesthetic, cosmic – also an important ethnic, community function, what activate the goal of the study. The communist leaders wanted Christianity to be faded from the public space, but it was summoned socially in the form of commemorations, so it leads the novelty of the investigation. There are several works devoted to religion in post communist Europe. The problematic relationship between the state and society, in all its forms of existence, and the religious phenomenon, between the temporal power and the transcendent power occupy a fundamental place in the sociological and historical thought. Patrick Michel, studying in his works on the specific issue of the relationship between religion the Church and totalitarian power, explains how much religion has suffered the hostile attitude of the power that tried to reduce its presence in the world social space he has just arrogated. It recalls the efforts of this one, to remain in the socio-political field, by refusing the rules of the political game introduced by the totalitarian power, by infiltrating inside the social field, in all its components, for to be present and participate in the existence of autonomous social spaces. In the Balkan countries, the image of a religion abused both by the identity and the political often revives with the discourse of post-communist religious renewal. In Bulgaria or Albania, there is this vision of religiosity completely stifled by the totalitarian regime. The vision of a religious emptiness imposed by the previous regime is specific to research on religious in the postcommunist era, a vision that emphasizes the repression of Christian religiosity and the resulting consequences for society. The researchers analyzed what happened during the socialist period and how religious life continued under the appearance of forced atheism. Conclusions. The biographical approach served as a starting point for field investigations aimed at documenting, from case-bycase reconstruction, stories of family trajectories, the multitute ritual solutions adopted during the communist period. I conducted exploratory surveys in Oltenia, the western part of Romanian Wallachia, which remained essentially a rural area, with the exception of the only big city of Craiova, (Oltenia's historical capital is the most important urban and administrative center district – 300,000 inhabitants) one of the largest cultural centers of the country. These first investigations that I conducted reveal the existence of a set of clandestine practices that were introduced, under the communist regime, to replace the absence of the Church in the main moments 16 Cioraianu Ce Ceausesco qui hante les Roumains, L’agence universitaire de la Francophonie [Ceausesco haunting Romanians, The University Agency of La Francophonie], Bucarest, 2004. 17 Brad I. «L’élu des élus» in Scanteia, 20 janvier, 1983. 18 «Mos Craciun 1947 à Craiova; Le Noel des hommes du travail”["Mos Craciun 1947 in Craiova; Christmas of the men of work "], „Inainte” 25.12.1947. 108 Iancu D. Daily life and religious holidays in Romania… related to the life cycle, especially for baptism and marriage, the prohibition of all religious attendance imposed on Party cadres, and the attempt to completely de-sacralize religious holidays. I also realized a work in the local archives of Oltenia, to expose the media of the time, the written press was the main means of the propagation of the new ideology. We had tried to expose the gradual way in which the communist system tried to impose the calendar that marked "the new era": we could distinguish the means used by the regime to manipulate the opinions and behavior of people regarding Religious holidays. These techniques of modeling the mentality of people are found abundantly in all the documents of that time. The effort to supplant the religious of daily life is also exerted on the celebration of festivals and calendar rites. The most followed restrictions are applied to Christic feasts (especially Christmas and Easter), while other festivals related to the commemoration of saints are recovered by the socialist ritual system. These are saints that the oral tradition has dedicated as patrons of economic activities (livestock, viticulture, beekeeping), a resource exploited by both the regime and the ordinary social actors. The Christian holiday becomes a folkloric entertainment.